1998
DOI: 10.3758/bf03199236
|View full text |Cite
|
Sign up to set email alerts
|

Social influence on avoidance of dangerous stimuli by rats

Abstract: Three experiments were conducted to determine whether a naive observer rat would avoid contact with a shock prod after watching a demonstrator rat contact, be shocked by, and defensively bury the prod. Wefound that observer rats took longer to contact prods that had delivered a shock to and been buried by a demonstrator rat than to contact prods that had not delivered shock and had not been buried. However, observer rats contacted prods buried by an unseen demonstrator rat or by an unseen experimenter with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Studies on observational aversive learning in rats failed to find blocking, latent inhibition and overshadowing-three well-documented features of classical conditioning [64]; however, studies in humans reported classical conditioning features for social aversive learning, including overshadowing and blocking [65], implying that observation might serve as a US.…”
Section: Observational and Social Learningmentioning
confidence: 99%
“…Studies on observational aversive learning in rats failed to find blocking, latent inhibition and overshadowing-three well-documented features of classical conditioning [64]; however, studies in humans reported classical conditioning features for social aversive learning, including overshadowing and blocking [65], implying that observation might serve as a US.…”
Section: Observational and Social Learningmentioning
confidence: 99%
“…Many species, including invertebrates, acquire emotionally neutral behaviors by observational learning [5, 10]. This process can also contribute to the acquisition of aversively-motivated behaviors [1, 19, 30, 35, 38], although not in all paradigms [6, 42]. Interestingly, unlike social modulation of pain hypersensitivity [24], observational learning is not limited to known conspecifics, and may be even intensified by observations of individuals of different strains [40].…”
Section: Introductionmentioning
confidence: 99%
“…Extant research across species suggests that observational fear learning draws upon similar neural circuitry to that of Pavlovian fear conditioning, although some notable differences between these types of learning have been documented (see Bennet, Galef, & Durlach, 1993;Lancet & Orr, 1980;White & Galef, 1998). The research reviewed here and elsewhere (Olsson et al, 2007) suggests the amygdala and the surrounding brain structures that mediate empathically driven appraisals of another's aversive experience support the learning and expression of observational fear.…”
Section: Resultsmentioning
confidence: 84%